Perbandingan Kinerja Routing Multi Copy Dan Routing First Contact Dengan Stationary Relay Node Pada Delay Tolerant Network (DTN) - Poltak G. Hutajulu; Widhi Yahya; Eko Sakti Pramukantoro (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Internet has become the most widely used as media presentations and information exchange. The information exchange can be accessed by using adequate connectivity. Some places still have low connectivity and some place do not have connectivity like Semeru mountain climbing areas, because of that the exchange of information will be difficult to access due to high delay and loss rate. The problem can be solved with Delay Tolerant Network (DTN). DTN is a network concept that is tolerant of delay and disconnected connections on a network. In this study using DTN network simulation process on The ONE simulator to compare the performance of DTN routing protocol with the addition of Stationary Relay Node. Routing types used are routing First Contact, Epidemic, MaxProp, ProPHET, and Spray and Wait with Semeru climbing scenarios. The results of this research show that the highest delivery probability is 0,5388 with 200 node and 15 Stationary Relay Node by Spray and Wait routing. The highest overhead ratio is 6.7484 with 50 nodes and 20 stationary relay nodes by Spray and routing. Routing First Contact before and after the addition of Stationary Relay Node has a higher average latency rate. The lowest average latency is 7491,9710 with 200 nodes and 15 Stationary Relay Nodes by MaxProp routing.